The library of D. Joaquín Gómez de la Cortina (1808-1868), Marquis of Morante. His repertoire in Peralada's Palace Library - Padrosa Gorgot, Inés (Revista General de Información y Documentación, 2023)
In Peralada's Palace Library are conserved copies with superlibris of different owners. Those belonging to D. Pedro Antonio de Aragón were recently unveiled. On this occasion, those that were owned by the Marquis de Morante, a renowned pedagogue, lawyer, writer and qualified as the best Spanish bibliophile of the 19th century, are detailed. He was decorated with different distinctions by the Queen Isabel II and decisive in the management of the University of Madrid, during the period in which was rector. Undoubtedly, his figure will have transcended for having assembled one of the best private libraries in Spain. His predilection for bibliophilia, his taste for aesthetics and his exquisiteness led him to commission bindings with his heraldic superlibris from the best nineteenth-century French representatives. His eagerness to collect led him not only to obtain more than 120,000 volumes, but also to write his Catalogus, a work that is a tribute to bibliography. Emphasis is placed on the dispersion of his bibliographical treasure as well as on the location of copies in libraries of different geographical points, which confirms that the precious intellectual legacy contributed by the Marquis has become world heritage.
Keywords: Joaquín Gómez de la Cortina; Marqués de Morante; University of Madrid; Rocabertí-Dameto; Miguel Mateu Pla; Carmen Mateu Quintana; Ernest Thorin (1834-1910); Heraldic bindings; Bookplates; Private libraries; Bibliophiles